Interactions of AChE with Aβ Aggregates in Alzheimer’s Brain: Therapeutic Relevance of IDN 5706 - Carvajal, Francisco J.; Inestrosa, Nibaldo C. (Frontiers in Molecular Neuroscience, 2011)
Acetylcholinesterase (AChE; EC 3.1.1.7) plays a crucial role in the rapid hydrolysis of the neurotransmitter acetylcholine, in the central and peripheral nervous system and might also participate in non-cholinergic mechanism related to neurodegenerative diseases. Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by a progressive deterioration of cognitive abilities, amyloid-β peptide (Aβ) accumulation and synaptic alterations. We have previously shown that AChE is able to accelerate the Aβ peptide assembly into Alzheimer-type aggregates increasing its neurotoxicity. Furthermore, AChE activity is altered in brain and blood of Alzheimer’s patients. The enzyme associated to amyloid plaques changes its enzymatic and pharmacological properties, as well as, increases its resistant to low pH, inhibitors and excess of substrate. Here, we reviewed the effects of IDN 5706, a hyperforin derivative that has potential preventive effects on the development of AD. Our results show that treatment with IDN5706 for 10 weeks increases brain AChE activity in seven month-old double transgenic mice (APPswe - PS1) and decreases the content of AChE associated with different types of amyloid plaques in this Alzheimer’s model. We concluded that early treatment with IDN 5706 decreases AChE-Aβ interaction and this effect might be of therapeutic interest in the treatment of AD.